New Evidence for the Contemporary Presence of Juvenile White Sharks (Carcharodon carcharias) in the Adriatic Sea - Patrick L. Jambura; Pero Ugarković; Mišo Pavičić; Ilija Ćetković; Simone Niedermüller; Jürgen Kriwet; Julia Türtscher (Fishes)
The presence of the white shark (Carcharodon carcharias) in the Mediterranean Sea is well documented, but mainly through historical and opportunistic records. Historically, the Adriatic Sea, particularly its eastern coastline, was considered a hotspot for white sharks, with relatively frequent reports of juvenile specimens suggesting a potential nursery area. However, since the second half of the 20th century, the abundance of white sharks in the Adriatic has experienced a dramatic decline, with the last confirmed sighting recorded in 2011. In this study, we report the recent capture of a young-of-the-year (YOY) white shark off the Croatian coast, previously misidentified as a porbeagle shark (Lamna nasus). In addition, we revisit historical records of white sharks in the Adriatic Sea to assess whether this region can be considered a nursery area. Our findings highlight significant gaps in the understanding of white shark spatial ecology and reproductive biology in the Mediterranean Sea. Furthermore, this study emphasizes the critical role citizen science and public engagement can play in documenting occurrences of these elusive and endangered predators, offering valuable insights for future conservation efforts.